Electro-Optic Upconversion in van der Waals Heterostructures via Nonequilibrium Photocarrier Tunneling - Linardy, Eric (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.